8ap^3=27y
Given: "8ap^3=27y" , where "p=\\frac{dy}{dx}"
Now "8ap^3=27y\n\\Rightarrow p^3=\\frac{27y}{8a}\n\\Rightarrow p^3-\\frac{27y}{8a}=0"
"\\Rightarrow p^3-(\\frac{3y^\\frac{1}{3}}{2a^\\frac{1}{3}})^3=0"
"\\Rightarrow (p-\\frac{3y^\\frac{1}{3}}{2a^\\frac{1}{3}})(p^2-\\frac{3y^\\frac{1}{3}}{2a^\\frac{1}{3}}p+\\frac{9y^\\frac{2}{3}}{4a^\\frac{2}{3}})=0"
"\\Rightarrow p=\\frac{3y^\\frac{1}{3}}{2a^\\frac{1}{3}}" , "p=\\frac{\\frac{3y^\\frac{1}{3}}{2a^\\frac{1}{3}}\\pm \\sqrt{\\frac{9y^\\frac{2}{3}}{4a^\\frac{2}{3}}-\\frac{9y^\\frac{2}{3}}{a^\\frac{2}{3}}}}{2}"
"\\Rightarrow p=\\frac{3y^\\frac{1}{3}}{2a^\\frac{1}{3}},p=\\frac{\\frac{3y^\\frac{1}{3}}{2a^\\frac{1}{3}}\\pm \\frac{3\\sqrt{3}y^\\frac{1}{3}}{2a^\\frac{1}{3}}i}{2}"
Observe that "p=\\frac{\\frac{3y^\\frac{1}{3}}{2a^\\frac{1}{3}}\\pm \\frac{3\\sqrt{3}y^\\frac{1}{3}}{2a^\\frac{1}{3}}i}{2}" are imaginary roots, so it can be discarded.
Now let ustake "p=\\frac{3y^\\frac{1}{3}}{2a^\\frac{1}{3}}"
"\\Rightarrow \\frac{dy}{dx}=\\frac{3y^\\frac{1}{3}}{2a^\\frac{1}{3}}"
Use separation of variables to solve the differential equation.
By using the separation of variables, we have
"\\frac{dy}{y^\\frac{1}{3}}=\\frac{3}{2a^\\frac{1}{3}}dx"
Integrating on both sides, we get
"\\int \\frac{dy}{y^\\frac{1}{3}}=\\frac{3}{2a^\\frac{1}{3}}\\int dx"
"\\Rightarrow \\frac{y^\\frac{2}{3}}{2\/3}=\\frac{3}{2a^\\frac{1}{3}}x+c"
"\\Rightarrow y^\\frac{2}{3}=xa^\\frac{-1}{3}+\\frac{2c}{3}"
"\\Rightarrow y^\\frac{2}{3}=xa^\\frac{-1}{3}+C,C=\\frac{2c}{3}"
Therefore, general solution is
"y-(xa^\\frac{-1}{3}+C)^\\frac{3}{2}=0"
Comments
Leave a comment